A NEW CORONAVIRUS INFECTION: FEATURES OF THE COURSE AND ISSUES OF VACCINATION IN CHILDREN (Literature review) (Herald of the National Children's Medical Center, 2022)
The article presents data from domestic and foreign literary sources on the pathogen, new strains, clinical variants and features of the course of a new coronavirus infection COVID-19 in children. The issues of vaccine prevention of this infection are also covered.
Keywords: COVID-19; children; vaccination; literature review